Making FAPE Appropriate Now for Students with Learning Disabilities. Issue 4 (29th August 2021) - Scanlon, David; Calhoon, Mary Beth; Berkeley, Sheri
Abstract: Since its inception, a premise of special education has been to provide students with disabilities with an appropriate education. The interpretation of appropriate has evolved across eras of special education. For students with learning disabilities, emphases on inclusion and high‐stakes achievement have eroded the intention of FAPE. It is time for a re‐envisioning of FAPE. A new vision should not presume the same outcomes for all. Restoring goals and individualized curriculum informed by the general education curriculum instead of exclusively focused "in the general education curriculum" is the way forward.